Tougher educational exam leading to worse selection - Eduardo de Carvalho Andrade; Luciano Irineu de Castro Filho (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2008)
This paper shows a somehow counterintuitive result: an increase in the exam difficulty may reduce the average quality (productivity) of selected individuals. Since the exam does not verify all skills, when its standard rises, candidates with relatively low skills emphasized in the test and high skills demanded in the job may no longer qualify. Hence, an increase in the testing standard may be counterproductive. One implication is that policies should emphasize alignment between the skills tested and those required in the actual jobs.
Keywords: I2; J24; 330; school standard; signaling model; cognitive skill; noncognitive ski